Preparation method and application of self-assembled copper nano-cluster
Self-assembled copper nanoclusters are prepared by ultrasonic mixing and magnetic stirring of copper salt and 4,6-dimethylthiopyrimidine in organic solvents, which solves the problems of few copper nanocluster synthesis methods and poor stability, achieving high efficiency and low Cost material preparation, suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411251646.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-11
- Filing Date
- 2024-09-08
- Publication Date
- 2024-12-13
AI Technical Summary
The synthesis methods of copper nanoclusters are few and harsh, which leads to challenges in large-scale production and stability, and lacks effective self-assembled copper nanocluster synthesis methods.
The mixed solution was ultrasonicated by copper salt and 4,6-dimethylthiopyrimidine in an organic solvent, and self-assembled copper nanoclusters were prepared by magnetic stirring and centrifugation steps, which simplified the preparation process and improved the stability and performance of the material.
It realizes high-efficiency and good stability self-assembly preparation of copper nanoclusters, significantly improving the fluorescence quantum efficiency and electrochemiluminescence efficiency of the material. It is suitable for catalysis, sensing, light emitting diodes and other fields, and is low in cost and can be prepared in large quantities. .
Smart Images

Figure CN119114955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel nano material preparation, and in particular relates to a preparation method of a self-assembled copper nanocluster and an application thereof. Background Art
[0002] Metal nanocluster materials are a type of ultra-small metal nanoparticles with a core-shell structure and a size of less than 2nm. Their cores are usually composed of several to hundreds of metal atoms. They have unique molecular-like electronic structures and unique optical and electrochemical properties. They are also low-toxic and have good biocompatibility. Therefore, they have attracted extensive attention in the fields of luminescence, catalysis, sensing, biomedicine, etc. The performance of metal nanoclusters is often closely related to the particle size and aggregate structure of the material. Compared with monodisperse nanoclusters, assembled metal nanoclusters have advantages such as excellent optical properties and good stability, and are suitable for application fields such as electrochemiluminescence and sensor devices. In addition, compared with precious metal nanoclusters (such as Au and Ag), copper nanoclusters have the advantages of relatively low price, low cost, and abundant reserves, which are suitable for large-scale applications.
[0003] Although copper nanoclusters have good application prospects in many fields, there are few synthesis methods for copper nanoclusters and the synthesis conditions are relatively harsh. Not only is the preparation cumbersome or requires additional operations such as heating, but the synthesized products have poor stability and are not suitable for long-term storage, making the large-scale production of copper nanoclusters challenging. Summary of the invention
[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention proposes a new method for preparing copper nanoclusters, and is a method for preparing self-assembled copper nanoclusters, which solves the problem that there are few methods for synthesizing copper nanoclusters or self-assembled copper nanoclusters in the prior art, and has the advantages of simple preparation process and large-scale preparation.
[0005] The present invention also provides a self-assembled copper nanocluster and its application. The self-assembled copper nanocluster prepared by the present invention is a new type of nanomaterial. Due to the existence of its self-assembly behavior, the structure of the material is significantly changed and the performance of the material is effectively improved.
[0006] Technical solution: In order to achieve the above-mentioned purpose, the method for preparing a self-assembled copper nanocluster of the present invention comprises the following steps:
[0007] (1) dissolving a copper salt in an organic solvent and ultrasonically forming a copper salt solution;
[0008] (2) dissolving 4,6-dimethylthiopyrimidine in an organic solvent and performing ultrasound to form a 4,6-dimethylthiopyrimidine solution;
[0009] (3) adding the 4,6-dimethylthiopyrimidine solution to the copper salt solution and stirring to obtain a mixed solution;
[0010] (4) The mixed solution is centrifuged to discard the supernatant, and the precipitate is washed to obtain self-assembled copper nanoclusters.
[0011] Wherein, the copper salt in step (1) is copper nitrate, copper sulfate, copper chloride or copper carbonate.
[0012] Preferably, the copper salt in step (1) is copper nitrate trihydrate.
[0013] Wherein, in step (1), 10 to 60 mg of copper salt powder is mixed with 5 mL of organic solvent to form a copper salt solution.
[0014] Preferably, 30 mg of copper nitrate trihydrate powder is mixed with 5 mL of ethanol to form a copper nitrate ethanol solution for later use.
[0015] Wherein, in step (2), 8 to 58 mg of 4,6-dimethylmercaptopyrimidine powder is mixed with 5 mL of an organic solvent to form a 4,6-dimethylmercaptopyrimidine solution.
[0016] Preferably, 28 mg of 4,6-dimethylmercaptopyrimidine powder is mixed with 5 mL of ethanol to form a 4,6-dimethylmercaptopyrimidine ethanol solution.
[0017] Wherein, the organic solvent in steps (1) and (2) is any one of methanol, ethanol, dimethyl sulfoxide and N,N-dimethylformamide, preferably ethanol.
[0018] Wherein, in step (3), the 4,6-dimethylthiopyrimidine solution is evenly added to the copper salt solution under magnetic stirring, and the magnetic stirring is continued for 3 to 20 minutes to obtain a mixed solution.
[0019] Preferably, the 4,6-dimethylthiopyrimidine ethanol solution is uniformly added to the copper nitrate ethanol solution under magnetic stirring, and the magnetic stirring is performed for 10 minutes to obtain a mixed solution.
[0020] Preferably, the mixed solution is centrifuged at 4500 rpm for 5 min, the supernatant is discarded, and the precipitate is washed with ethanol.
[0021] In step (4), the mixed solution is centrifuged at 1000-6000 rpm for 5 min, the supernatant is discarded, and the precipitate is washed to obtain self-assembled copper nanoclusters (SA-DMPM-CuNCs). In step (4), 5-30 mL of water is added to the precipitate, and magnetic stirring is performed for 10-80 min to obtain a self-assembled copper nanocluster suspension.
[0022] Preferably, 10 mL of water is added to the precipitate and magnetic stirring is performed for 10 to 80 min to obtain the self-assembled copper nanocluster suspension. More preferably, 10 mL of water is added to the precipitate and magnetic stirring is performed for 60 min.
[0023] The self-assembled copper nanoclusters are prepared by the method for preparing the self-assembled copper nanoclusters of the present invention.
[0024] The self-assembled copper nanoclusters prepared by the method for preparing the self-assembled copper nanoclusters of the present invention are used in catalysis, fluorescence (imaging) sensing, light-emitting diodes, photoelectric conversion materials and biomedicine.
[0025] Preferably, the self-assembled copper nanoclusters are used in the preparation of an electrochemiluminescence sensor for detecting alkaline phosphatase.
[0026] Wherein, the electrochemiluminescent sensor is formed by modifying manganese dioxide nanosheets onto an electrode with an electrochemiluminescent reagent self-assembled copper nanoclusters as a base film layer. In the present invention, alkaline phosphatase (ALP) is first catalyzed with the substrate L-ascorbic acid 2-phosphate trisodium salt (AAP) to produce a large amount of intermediate ascorbic acid (AA); then the intermediate AA is quantitatively detected by the electrochemiluminescent sensor of the present invention, and the purpose of indirect quantitative detection of alkaline phosphatase is finally achieved. In the present invention, self-assembled copper nanoclusters are used as electrochemiluminescent reagents, and triethylamine is used as a co-reactant of the electrochemiluminescent reaction, wherein the self-assembled copper nanoclusters have the advantages of low toxicity, good stability, high electrochemiluminescence intensity, and the like, and have the advantages of a simple preparation process and can be prepared in large quantities. The sensor system of the present invention performs quantitative detection of alkaline phosphatase in human serum, and has good specificity, high sensitivity, wide linear range, and has the advantages of low cost. The electrochemical sensor prepared by using the self-assembled copper nanoclusters of the present invention has high sensitivity, and solves the problem of low sensitivity of the existing commercial alkaline phosphatase detection kit (spectrophotometry, the minimum detection limit is 3U / L).
[0027] Preferably, the method for preparing the electrochemiluminescent sensor for measuring AA and alkaline phosphatase of the present invention comprises the following steps:
[0028] (1) After polishing the working electrode, ultrasonic cleaning is performed;
[0029] (2) dropping the SA-DMPM-CuNCs suspension onto the surface of the working electrode and leaving it to dry at room temperature;
[0030] (3) A manganese dioxide nanosheet solution was added dropwise to the surface of the electrode and allowed to stand and dry at room temperature to obtain an electrochemiluminescent sensor for measuring AA and alkaline phosphatase.
[0031] More preferably, the preparation method of the electrochemiluminescent sensor for measuring AA and alkaline phosphatase is prepared according to the following steps:
[0032] (1) The working electrode was polished with 0.3 μm and 0.05 μm Al2O3 powders, and then ultrasonically cleaned with water, ethanol, and water for 2 to 10 min.
[0033] (2) taking 2-20 μL of 0.1-1 mg / mL SA-DMPM-CuNCs suspension and dropping it onto the surface of the working electrode and letting it stand to dry at room temperature;
[0034] (3) 2 to 20 μL of 0.01 to 1 mg / mL manganese dioxide nanosheet solution was added dropwise to the electrode surface and allowed to stand at room temperature to dry, thereby obtaining an electrochemiluminescent sensor for measuring AA and alkaline phosphatase.
[0035] Most preferably, the preparation method of the electrochemiluminescent sensor for measuring AA and alkaline phosphatase is prepared according to the following steps:
[0036] (1) The working electrode was polished with 0.3 μm and 0.05 μm Al2O3 powders, and then ultrasonically cleaned with water, ethanol, and water for 5 min;
[0037] (2) Take 5 μL of 0.24 mg / mL SA-DMPM-CuNCs suspension and drop it onto the surface of the working electrode and let it stand and dry at room temperature;
[0038] (3) 5 μL of 0.1 mg / mL manganese dioxide nanosheet solution was added dropwise to the electrode surface and allowed to stand at room temperature to dry, thereby obtaining an electrochemiluminescent sensor for measuring AA and alkaline phosphatase.
[0039] Wherein, the steps of quantifying alkaline phosphatase are as follows:
[0040] (1) preparing a mixed solution of L-ascorbic acid 2-phosphate trisodium salt (AAP) and alkaline phosphatase using a Tris-HCl buffer solution;
[0041] (2) mixing the above solutions and reacting them at 37° C. to obtain a solution containing AA;
[0042] (3) placing the electrochemiluminescent sensor of claim 1 in the solution containing AA obtained in (2) to react at room temperature, taking it out, washing it, and drying it for later use;
[0043] (4) Collecting the ECL signal intensity of the electrochemiluminescence sensor after the reaction in step (3), and calculating the corresponding alkaline phosphatase concentration according to the recovery value of the electrochemiluminescence signal.
[0044] The electrochemiluminescence sensor after the reaction in step (3) is connected to an ECL instrument, and a PBS solution with a pH of 6 to 10 is used as an electrolyte and 10 to 150 μM triethylamine is used as a co-reactant to collect the ECL signal intensity, and the corresponding alkaline phosphatase concentration is calculated by the recovery value of the electrochemiluminescence signal.
[0045] The electrochemiluminescent sensor for measuring alkaline phosphatase of the present invention is used in preparing a tool or reagent for quantitatively detecting alkaline phosphatase.
[0046] Preferably, the application of the quantitative detection of alkaline phosphatase comprises the following detection steps:
[0047] (1) preparing a mixture of L-ascorbic acid 2-phosphate trisodium salt (AAP) and alkaline phosphatase using a Tris-HCl buffer solution with a pH of 7 to 10;
[0048] (2) mixing the above solutions and reacting them at 37° C. for 10 to 60 minutes to obtain a solution containing AA;
[0049] (3) placing the electrochemiluminescence sensor in the solution obtained in (2) to react at room temperature for 1 to 10 minutes, taking it out, washing it with water, and blowing it dry with nitrogen for later use.
[0050] (4) Connecting the electrochemiluminescence sensor after the reaction in step (3) to an ECL instrument to collect the ECL signal intensity, and calculating the corresponding alkaline phosphatase concentration according to the recovery value of the electrochemiluminescence signal.
[0051] More preferably, the quantitative detection of alkaline phosphatase is carried out according to the following steps:
[0052] (1) a mixture containing 25 mM AAP and different concentrations of alkaline phosphatase was prepared using a Tris-HCl buffer solution at pH 7 to 10;
[0053] (2) mixing the above solutions and reacting them at 37° C. for 10 to 60 minutes to obtain a solution containing AA;
[0054] (3) The electrochemiluminescence sensor is placed in the solution obtained in (2) to react at room temperature for 1 to 10 minutes, then taken out, washed with water, and blown dry with nitrogen for later use.
[0055] (4) Connecting the electrochemiluminescence sensor after the reaction in step (3) to an ECL instrument, using a PBS solution with a pH of 6 to 10 as an electrolyte and 10 to 150 μM triethylamine as a co-reactant, collecting the ECL signal intensity, and calculating the corresponding alkaline phosphatase concentration based on the recovery value of the electrochemiluminescence signal.
[0056] Most preferably, the quantitative detection of alkaline phosphatase is performed according to the following steps:
[0057] (1) A mixture containing 25 mM AAP and different concentrations of alkaline phosphatase was prepared using a Tris-HCl buffer solution at pH 8;
[0058] (2) mixing the above solutions and reacting them at 37°C for 30 min to obtain a solution containing AA;
[0059] (3) The electrochemiluminescence sensor was placed in the solution obtained in (2) to react at room temperature for 3 minutes, and then washed with water and dried with nitrogen for later use.
[0060] (4) Connect the electrochemiluminescence sensor after the reaction in step (3) to an ECL instrument, use a PBS solution with pH = 7.4 as an electrolyte and 75 μM triethylamine as a co-reactant, collect the ECL signal intensity, and calculate the corresponding alkaline phosphatase concentration based on the recovery value of the electrochemiluminescence signal.
[0061] The photomultiplier high voltage (PMT) for collecting the ECL signal intensity is 300-800V, and the test range is 0.2-1.3V.
[0062] Preferably, when collecting the ECL signal intensity, PMT=500V, and the test range is 0.2-1.3V.
[0063] When the electrochemical sensor prepared by the present invention uses self-assembled copper nanoclusters (SA-DMPM-CuNCs) as an electrochemiluminescent reagent, manganese dioxide nanosheets are used as an ECL signal quencher of the luminescent agent SA-DMPM-CuNCs, triethylamine is used as a co-reactant of the electrochemiluminescent reaction, and the electrochemiluminescent signal is detected by an electrochemiluminescence workstation.
[0064] The present invention also provides an electrochemiluminescence composition system, including self-assembled copper nanoclusters as electrochemiluminescence reagents, manganese dioxide nanosheets as ECL signal quenchers of the luminescent agent SA-DMPM-CuNCs, triethylamine as a co-reactant of the electrochemiluminescence reaction, and a three-electrode system.
[0065] Preferably, the electrochemiluminescence composition system includes SA-DMPM-CuNCs as an electrochemiluminescent agent, manganese dioxide nanosheets as an ECL signal quencher of the luminescent agent SA-DMPM-CuNCs, triethylamine as a co-reactant of the electrochemiluminescence reaction, a glassy carbon electrode as a working electrode, a silver-silver chloride electrode as a reference electrode, and a platinum wire electrode as an auxiliary electrode.
[0066] In the present invention, ALP first undergoes a catalytic reaction with the substrate AAP to produce a large amount of intermediate AA; then the intermediate AA is quantitatively detected by the electrochemiluminescence sensor of the present invention, and finally the purpose of indirect quantitative detection of alkaline phosphatase is achieved. When ALP is specifically detected, ALP is catalytically reacted with the substrate AAP to produce a large amount of intermediate AA; the manganese dioxide nanosheets are used as the ECL signal quencher of the luminescent agent SA-DMPM-CuNCs, first quenching the ECL signal of the sensor, and then an oxidation-reduction reaction occurs under the action of the intermediate AA to generate Mn 2+ , thereby restoring the ECL signal of the sensor; since AA can reduce manganese dioxide nanoparticles in a dose-dependent manner, the concentration of ALP is linearly related to the electrochemiluminescence signal recovery value, realizing the quantitative detection of ALP.
[0067] The present invention mainly proposes a new preparation method for the currently difficult preparation of self-assembled copper nanoclusters or the complicated preparation method. The self-assembled copper nanoclusters prepared by the present invention, although belonging to copper nanoclusters, are new self-assembled copper nanocluster materials with better performance. The self-assembled copper nanoclusters of the present invention are self-assembled copper nanoclusters (SA-DMPM-CuNCs) prepared by using 4,6-dimethylthiopyrimidine (DMPM) as ligands, and their self-assembly characteristics can be regulated and the material performance can be improved. They can replace traditional copper nanocluster materials and be applied to catalysis, fluorescence (imaging) sensing, light-emitting diodes, electrochemical sensing, photoelectric conversion materials, biomedicine and other fields, and the synthesis method is novel, and the obtained material has high stability and good biocompatibility.
[0068] Currently, self-assembly is one of the effective strategies to design ideal building blocks to optimize the performance of nanoclusters. Appropriate self-assembly to connect nanoclusters can produce ordered structures, which will be beneficial to improve electron / charge transfer, inhibit the movement and rotation of nanocluster ligands, and reduce the oxidation of nanoclusters. Intermolecular interactions, especially those involving π-π stacking, are crucial for regulating molecular aggregation and material properties. Since pyrimidine derivatives have a strong tendency to form π-π stacking assemblies and excellent electron transfer properties, we use them as ligands for the synthesis of CuNCs to improve their stability and electron transport properties.
[0069] The present invention adopts a brand-new method to successfully synthesize copper nanoclusters with high stability, significant fluorescence quantum efficiency and electrochemical luminescence efficiency. The self-assembly mechanism of the self-assembled copper nanoclusters (SA-DMPM-CuNCs) of the present invention is as follows: the copper nanoclusters (DMPM-CuNCs) before self-assembly realize surface motif reconstruction in H2O, resulting in an increase in the relative Cu(I) content, thereby generating strong inter-cluster copper-philic Cu(I)···Cu(I) interactions, which promotes the self-assembly of the CuNCs core. On the other hand, the π-π stacking and hydrophobic interaction of the DMPM ligands lead to the self-assembly of the ligands, further bringing the CuNCs closer to each other. Both of these factors contribute to the transformation of DMPM-CuNCs into ordered SA-DMPM-CuNCs in aqueous solution.
[0070] The present invention proposes for the first time to use 4,6-dimethyl-2-mercaptopyrimidine (DMPM) small conjugated molecules as ligands to simply synthesize SA-DMPM-CuNCs with high stability, significant fluorescence quantum efficiency and electrochemical luminescence efficiency at room temperature. The new preparation method of the present invention is not only simple to prepare, but also does not require additional conditions such as specific reaction containers and temperature increase, and can be simply and quickly synthesized at room temperature under normal pressure.
[0071] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0072] 1. The present invention prepares a novel self-assembled copper nanocluster (SA-DMPM-CuNCs). Transmission electron microscopy images show that the SA-DMPM-CuNCs have a nanosheet morphology, and regular arrangement of single particle clusters can be seen on the nanosheets, which is different from the traditional monodisperse cluster morphology, so it is a self-assembled type.
[0073] 2. The present invention provides a new method for preparing self-assembled copper nanoclusters, which solves the problems of few synthesis methods and complicated steps of self-assembled copper nanoclusters in the prior art, and has the advantages of simple preparation process and large-scale preparation.
[0074] 3. The self-assembled copper nanoclusters prepared by the present invention are a new type of nanomaterial with the advantages of good stability, high fluorescence quantum efficiency (39.3%) and high electrochemical luminescence efficiency (20%), which are significantly better than the performance of traditional copper nanoclusters. The self-assembled copper nanoclusters prepared by the present invention significantly change the structure of the material due to the existence of assembly behavior, and effectively improve the performance of the material. Therefore, they have important application value in related fields such as catalysis, fluorescence (imaging) sensing, light-emitting diodes, electrochemical sensing, photoelectric conversion materials and biomedicine.
[0075] 4. The present invention provides a new application of the prepared self-assembled copper nanocluster (SA-DMPM-CuNCs) material as an electrochemiluminescence reaction luminescent agent. As an electrochemiluminescence luminescent agent, it has good stability, high electrochemiluminescence efficiency, and a simple preparation process. It can be prepared in large quantities and can be effectively applied to electrochemiluminescence sensors to achieve high-sensitivity sensing.
[0076] 5. The present invention uses the self-assembled copper nanoclusters (SA-DMPM-CuNCs) material as the electrochemiluminescent reaction luminescent agent to detect alkaline phosphatase in serum, which does not require complex sample processing and avoids the use of expensive instruments and cumbersome operations. At the same time, the present invention designs an "on-off-on" type electrochemiluminescent sensor based on the specificity of the target analyte ALP. The sensor of the present invention successfully realizes the quantitative detection of ALP in human serum, and has good specificity, high sensitivity, wide linear range, low cost, and convenient use. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 Transmission electron microscopy image of DMPM-CuNCs.
[0078] Figure 2 Transmission electron microscopy images and high-resolution transmission electron microscopy images of SA-DMPM-CuNCs.
[0079] Figure 3 Transmission electron microscopy images of DMPM-CuNCs dispersed in water for (a) 5 s, (b) 1 min, (c) 5 min, (d) 10 min, (e) 30 min, and (f) 60 min, respectively.
[0080] Figure 4 Fluorescence spectra of DMPM-CuNCs dispersed in water for (a) 5s, (b) 1min, (c) 5min, (d) 10min, (e) 30min and (f) 60min, respectively.
[0081] Figure 5 High-resolution X-ray photoelectron spectroscopy-copper spectrum of DMPM-CuNCs and SA-DMPM-CuNCs.
[0082] Figure 6 X-ray photoelectron spectroscopy copper Auger spectra of DMPM-CuNCs and SA-DMPM-CuNCs.
[0083] Figure 7 High-resolution X-ray photoelectron spectroscopy-sulfur spectra of DMPM-CuNCs and SA-DMPM-CuNCs.
[0084] Figure 8(a) UV absorption and (b) fluorescence spectra of DMPM-CuNCs and SA-DMPM-CuNCs.
[0085] Fig. 9 The photostability diagram of SA-DMPM-CuNCs after irradiation with 345 nm ultraviolet light for 3500 s.
[0086] Fig.10 The fluorescence spectrum changes of SA-DMPM-CuNCs stored in air for 14 days.
[0087] Fig.11 Thermogravimetric analysis diagrams of (a) DMPM-CuNCs and (b) SA-DMPM-CuNCs.
[0088] Fig.12 (a) Amperometric Qt curve and (b) wavelength-resolved ECL spectrum of the ECL reaction between SA-DMPM-CuNCs and Ru(bpy)3Cl2.
[0089] Fig.13 Schematic diagram of the detection process of the ECL biosensor for ALP sensing.
[0090] Fig.14 (a) Electrochemical impedance spectroscopy and (b) ECL spectroscopy for the sensor step-by-step construction.
[0091] Fig.15 This is a linear relationship analysis diagram between the sensor △ECL signal intensity and the logarithmic value of alkaline phosphatase.
[0092] Fig.16 Figure 2 is a diagram of sensor selectivity.
[0093] Fig.17 This is the result of serum spike recovery test. DETAILED DESCRIPTION
[0094] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0095] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions specified in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0096] Example 1
[0097] A preparation method of self-assembled copper nanoclusters (SA-DMPM-CuNCs) comprises the following steps: S1, uniformly mixing 10 mg of copper nitrate trihydrate powder and 5 mL of ethanol by ultrasonic mixing to form a blue copper nitrate ethanol solution; S2, uniformly mixing 8 mg of 4,6-dimethylthiopyrimidine powder and 5 mL of ethanol by ultrasonic mixing to form a light yellow 4,6-dimethylthiopyrimidine ethanol solution; S3, uniformly adding the 4,6-dimethylthiopyrimidine ethanol solution to the copper nitrate ethanol solution under 500 rpm magnetic stirring at room temperature, stirring for 3 minutes, and obtaining a mixed solution; S4, centrifuging the mixed solution under 1000 rpm for 5 minutes, discarding the supernatant, and washing the precipitate with ethanol to obtain DMPM-CuNCs; S5, adding 5 mL of water to the precipitate, and magnetically stirring for 10 minutes to obtain a self-assembled copper nanocluster suspension.
[0098] Example 2
[0099] A self-assembled copper nanocluster (SA-DMPM-CuNCs) comprises the following steps: S1, uniformly mixing 20 mg of copper nitrate trihydrate powder and 5 mL of ethanol by ultrasonic mixing to form a blue copper nitrate ethanol solution; S2, uniformly mixing 18 mg of 4,6-dimethylthiopyrimidine powder and 5 mL of ethanol by ultrasonic mixing to form a light yellow 4,6-dimethylthiopyrimidine ethanol solution; S3, uniformly adding the 4,6-dimethylthiopyrimidine ethanol solution to the copper nitrate ethanol solution under 800 rpm magnetic stirring at room temperature, stirring for 7 minutes, and obtaining a mixed solution; S4, centrifuging the mixed solution under 2000 rpm for 5 minutes, discarding the supernatant, and washing the precipitate with ethanol to obtain DMPM-CuNCs; S5, adding 8 mL of water to the precipitate, and magnetically stirring for 20 minutes to obtain a self-assembled copper nanocluster suspension.
[0100] Example 3
[0101] A self-assembled copper nanocluster (SA-DMPM-CuNCs) comprises the following steps: S1, uniformly mixing 30 mg of copper nitrate trihydrate powder and 5 mL of ethanol by ultrasonic mixing to form a blue copper nitrate ethanol solution; S2, uniformly mixing 28 mg of 4,6-dimethylthiopyrimidine powder and 5 mL of ethanol by ultrasonic mixing to form a light yellow 4,6-dimethylthiopyrimidine ethanol solution; S3, uniformly adding the 4,6-dimethylthiopyrimidine ethanol solution to the copper nitrate ethanol solution under 1000 rpm magnetic stirring at room temperature, stirring for 10 minutes, and obtaining a mixed solution; S4, centrifuging the mixed solution at 4000 rpm for 5 minutes, discarding the supernatant, and washing the precipitate with ethanol to obtain DMPM-CuNCs; S5, adding 10 mL of water to the precipitate, and magnetically stirring for 60 minutes to obtain a self-assembled copper nanocluster suspension.
[0102] The transmission electron microscopy images and high-resolution transmission electron microscopy images of the copper nanoclusters (DMPM-CuNCs) before self-assembly and the self-assembled copper nanoclusters (SA-DMPM-CuNCs) prepared in Example 3 are shown in FIG. Figure 1 and Figure 2 As shown. The originally random and disordered aggregates turned into ordered and regular nanosheet structures after assembly, and these nanosheets were composed of orderly arranged single nanoclusters with an average diameter of 0.3-0.5nm. In order to further study its assembly process, transmission electron microscopy was used to monitor the morphological transformation at different reaction times (5s-60min) ( Figure 3 ) and recorded the fluorescence spectrum changing with time ( Figure 4 After DMPM-CuNCs were dispersed in water (with the same concentration as that of the self-assembled copper nanocluster suspension prepared in Example 3), DMPM-CuNCs gradually transformed into highly ordered nanosheets. At the same time, the fluorescence intensity increased with time, and the maximum wavelength had a slight blue shift, indicating that the assembly inhibited the molecular vibration and rotation of the ligand, thereby hindering the non-radiative transition, resulting in enhanced fluorescence emission ( Figure 3 and Figure 4 ). The Cu2p high-resolution X-ray photoelectron spectra and Auger electron spectra of DMPM-CuNCs and SA-DMPM-CuNCs are shown in Figure 2. Figure 5 and Figure 6 As shown in the figure, no satellite peak of Cu(II) (around 942.0 eV) was observed for DMPM-CuNCs and SA-DMPM-CuNCs, indicating that DMPM fully reduced Cu(II) to Cu(I) and Cu(0) during the formation of nanoclusters. In addition, the Cu LMM Auger spectrum showed that the molar ratios of Cu(I) / Cu(0) were 2.02 and 2.22, respectively, indicating that the Cu(I) species increased after self-assembly. The S2p high-resolution X-ray photoelectron spectrum is shown in the figure. Figure 7 As shown, indicating the formation of Cu-S bonds. Figures 1 to 7 It is proved that the present invention successfully synthesized self-assembled copper nanoclusters.
[0103] UV-Visible Spectroscopy ( Figure 8 a) SA-DMPM-CuNCs has a main absorption peak at 324 nm, which is significantly red-shifted compared with DMPM-CuNCs, indicating that the π-π stacking of DMPM after assembly enhances the electronic conjugation; in addition, self-assembly significantly improves the fluorescence emission intensity of SA-DMPM-CuNCs, as shown in Figure 8As shown in Fig. b, when excited at 345 nm, DMPM-CuNCs did not emit light, while SA-DMPM-CuNCs showed strong fluorescence emission at 680 nm, with an absolute quantum yield of 39.3%, while the fluorescence quantum yield of self-assembled copper nanoclusters in the prior art was only 15.4%, (J.Am.Chem.Soc.2017,139,4318-4321). The effect of the present invention is significantly improved. At the same time, SA-DMPM-CuNCs showed excellent oxidation stability, light stability and thermal stability, such as Fig. 9 and Fig.10 As shown in the figure, after irradiation with 345nm ultraviolet light for 3500s or storage in air for 14d, the fluorescence of SA-DMPM-CuNCs has little decay. This excellent stability may be due to the tight packing of ligands that hinders the oxidation of Cu(0) / Cu(I) in CuNCs. Thermogravimetric analysis ( Fig.11 ) The thermal stability of CuNCs before and after assembly was further studied. The results showed that the severe decomposition temperature of DMPM-CuNCs was 250°C, while the severe decomposition temperature of SA-DMPM-CuNCs was significantly increased to above 360°C, indicating that the thermal stability of SA-DMPM-CuNCs after assembly was significantly improved. Using wavelength-resolved electrochemiluminescence spectroscopy, the ECL efficiency of SA-DMPM-CuNCs was determined to be 20% ( Fig.12 ), the specific calculation process is as follows:
[0104]
[0105] Where “ECL” and “Current” represent the integrated ECL photon number obtained from the corrected ECL spectrum according to the counting sensitivity of the photomultiplier tube at different light wavelengths and Faraday electrochemical current values, respectively, where “st” represents the Ru(bpy)3Cl2 standard, “x” represents SA-DMPM-CuNCs, and “t” represents the test time.
[0106] The above experiments effectively prove that the self-assembled copper nanoclusters prepared by the present invention can be used as luminescent agents with excellent performance.
[0107] Example 4
[0108] A self-assembled copper nanocluster (SA-DMPM-CuNCs) comprises the following steps: S1, uniformly mixing 40 mg of copper nitrate trihydrate powder with 5 mL of ethanol by ultrasonication to form a blue copper nitrate ethanol solution; S2, uniformly mixing 38 mg of 4,6-dimethylthiopyrimidine powder with 5 mL of ethanol by ultrasonication to form a light yellow 4,6-dimethylthiopyrimidine ethanol solution; S3, uniformly adding the 4,6-dimethylthiopyrimidine ethanol solution to the copper nitrate ethanol solution under 1200 rpm magnetic stirring at room temperature, stirring for 13 minutes, and obtaining a mixed solution; S4, centrifuging the mixed solution under 5000 rpm for 5 minutes, discarding the supernatant, and washing the precipitate with ethanol to obtain DMPM-CuNCs; S5, adding 10 mL of water to the precipitate, and magnetically stirring for 40 minutes to obtain a self-assembled copper nanocluster suspension.
[0109] Example 5
[0110] A self-assembled copper nanocluster (SA-DMPM-CuNCs) comprises the following steps: S1, uniformly mixing 50 mg of copper nitrate trihydrate powder and 5 mL of ethanol by ultrasonic mixing to form a blue copper nitrate ethanol solution; S2, uniformly mixing 48 mg of 4,6-dimethylthiopyrimidine powder and 5 mL of ethanol by ultrasonic mixing to form a light yellow 4,6-dimethylthiopyrimidine ethanol solution; S3, uniformly adding the 4,6-dimethylthiopyrimidine ethanol solution to the copper nitrate ethanol solution under 1400 rpm magnetic stirring at room temperature, stirring for 17 minutes, and obtaining a mixed solution; S4, centrifuging the mixed solution under 6000 rpm for 5 minutes, discarding the supernatant, and washing the precipitate with ethanol to obtain DMPM-CuNCs; S5, adding 200 mL of water to the precipitate, and magnetically stirring for 60 minutes to obtain a self-assembled copper nanocluster suspension.
[0111] Example 6
[0112] A self-assembled copper nanocluster (SA-DMPM-CuNCs) comprises the following steps: S1, uniformly mixing 60 mg of copper nitrate trihydrate powder and 5 mL of ethanol by ultrasonic mixing to form a blue copper nitrate ethanol solution; S2, uniformly mixing 58 mg of 4,6-dimethylthiopyrimidine powder and 5 mL of ethanol by ultrasonic mixing to form a light yellow 4,6-dimethylthiopyrimidine ethanol solution; S3, uniformly adding the 4,6-dimethylthiopyrimidine ethanol solution to the copper nitrate ethanol solution under 1500 rpm magnetic stirring at room temperature, stirring for 20 minutes, and obtaining a mixed solution; S4, centrifuging the mixed solution under 6000 rpm for 10 minutes, discarding the supernatant, and washing the precipitate with ethanol to obtain DMPM-CuNCs; S5, adding 30 mL of water to the precipitate, and magnetically stirring for 80 minutes to obtain a self-assembled copper nanocluster suspension.
[0113] Comparative Example 1
[0114] According to the method of Example 3, except that the water in step 5 of Example 3 of the present invention is replaced by: N,N-dimethylformamide, methanol, dimethyl sulfoxide, capronitrile, acetone, chloroform, ethyl acetate, tetrahydrofuran, n-butanol, toluene, cyclohexane, ethane, etc., the target product cannot be synthesized. For example, when dimethyl sulfoxide is used instead, the fluorescence quantum efficiency is reduced to 4.3%, and the product is different.
[0115] Comparative Example 2
[0116] The method of Example 3 was followed, except that the ligand 4,6-dimethylmercaptopyrimidine (DMPM) was replaced with 4-amino-6-hydroxy-2-mercaptopyrimidine, 6-amino-2-mercaptopyrimidine, 4,6-diamino-2-mercaptopyrimidine, etc.; the target product could not be successfully synthesized.
[0117] Example 7
[0118] The preparation method of the electrochemiluminescence sensor for measuring AA comprises the following steps: S1, polishing the glassy carbon working electrode (3 mm) with 0.3 μm and 0.05 μm Al2O3 powders in sequence, and then ultrasonically cleaning with water, ethanol and water for 5 min in sequence; S2, taking 5 μL of the 0.24 mg / mL SA-DMPM-CuNCs suspension prepared in Example 3 and dropping it on the surface of the working electrode with a diameter of 3 mm, and standing it to dry at room temperature; S3, dropping 5 μL of 0.1 mg / mL manganese dioxide nanosheet (CAS No.: 1313-13-9, Merck No. 918040) solution on the surface of the electrode, and standing it to dry at room temperature to obtain an electrochemiluminescence sensor for measuring AA, which can also be used as an electrochemical sensor for subsequent detection of alkaline phosphatase.
[0119] Example 8
[0120] The preparation method of the electrochemiluminescence sensor for measuring AA comprises the following steps: S1, polishing the glassy carbon working electrode (3 mm) with 0.3 μm and 0.05 μm Al2O3 powders in sequence, and then ultrasonically cleaning with water, ethanol and water for 5 min in sequence; S2, dropping 10 μL of the 0.5 mg / mL SA-DMPM-CuNCs suspension prepared in Example 3 onto the surface of the working electrode, and standing to dry at room temperature; S3, dropping 10 μL of 0.2 mg / mL manganese dioxide nanosheet solution onto the surface of the electrode, and standing to dry at room temperature to obtain an electrochemiluminescence sensor for measuring AA, which can also be used as an electrochemical sensor for subsequent detection of alkaline phosphatase.
[0121] Example 9
[0122] The preparation method of the electrochemiluminescence sensor for measuring AA comprises the following steps: S1, polishing the glassy carbon working electrode (3 mm) with 0.3 μm and 0.05 μm Al2O3 powders in sequence, and then ultrasonically cleaning with water, ethanol and water for 5 min in sequence; S2, dropping 5 μL of the 0.5 mg / mL SA-DMPM-CuNCs suspension prepared in Example 3 onto the surface of the working electrode, and standing to dry at room temperature; S3, dropping 10 μL of 0.5 mg / mL manganese dioxide nanosheet solution onto the surface of the electrode, and standing to dry at room temperature to obtain an electrochemiluminescence sensor for measuring AA, which can also be used as an electrochemical sensor for subsequent detection of alkaline phosphatase.
[0123] Example 10
[0124] The detection process of the electrochemiluminescence sensor system for determining alkaline phosphatase is as follows: S1, 300 μL of a mixed solution containing 25 mM AAP solution and alkaline phosphatase of different concentrations is prepared with a Tris-HCl buffer solution of pH=8; S2, the above solutions are mixed and reacted at 37°C for 30 minutes to obtain a solution containing AA; S3, the electrochemiluminescence sensor prepared in Example 7 is placed in the solution obtained in the above S2 and soaked at room temperature for reaction for 3 minutes, taken out, washed with water, and blown dry with nitrogen for standby use; S4, the electrochemiluminescence sensor after the reaction in step S3 is connected to an ECL instrument as a working electrode, a silver-silver chloride electrode as a reference electrode, a platinum wire electrode as an auxiliary electrode, a PBS solution of pH=7.4 as an electrolyte and 75 μM triethylamine as a co-reactant, and the ECL signal intensity is collected, the PMT is 500V, the potential range is 0.2-1.3V, the recovery value of the electrochemiluminescence signal is calculated, and the corresponding alkaline phosphatase concentration is calculated according to the standard curve.
[0125] Example 10 The schematic diagram of the detection process of the electrochemiluminescence sensor system is as follows Fig.13 To demonstrate the successful construction of the proposed biosensor, electrochemical impedance spectroscopy (EIS) tests were performed step by step. Fig.14 a). The results show that after coating the GCE surface with SA-DMPM-CuNCs, the charge transfer resistance increased significantly, and the subsequent addition of MnO2 nanosheets led to a significant decrease in the interfacial impedance, indicating that MnO2 can enhance the conductivity and promote charge transport. After the introduction of ALP-catalyzed AA, the MnO2 layer was reduced to Mn 2 + And released from the electrode surface, resulting in a significant increase in charge transfer resistance. In addition, the ECL test of the sensor construction process showed that the construction of the sensor is feasible ( Fig.14b). After the bare GCE was modified with SA-DMPM-CuNCs, an obvious ECL signal was observed, indicating that the sensor had good ECL performance. After MnO2 modification, the ECL intensity of SA-DMPM-CuNCs decreased significantly, due to the strong ECL resonance energy transfer (ECL-RET) effect between SA-DMPM-CuNCs and MnO2, which hindered the charge transfer between the luminescent reagent and the co-reactant. However, the addition of ALP caused the redox reaction of MnO2 with the AAP product (AA), and the ECL intensity gradually recovered. These results indicate that the ECL sensing platform for ALP detection was successfully prepared.
[0126] Embodiment 11
[0127] The detection process of the electrochemiluminescence sensor system for determining alkaline phosphatase is as follows: S1, using a Tris-HCl buffer solution with a pH of 9 to prepare 300 μL of a mixed solution containing a 25 mM AAP solution and alkaline phosphatase of different concentrations; S2, mixing the above solutions and reacting them at 37° C. for 50 min to obtain a solution containing AA; S3, placing the electrochemiluminescence sensor in the solution obtained in the step S2 to react at room temperature for 5 min, taking it out, washing it with water, and blowing it dry with nitrogen for standby use; S4, connecting the electrochemiluminescence sensor after the reaction in step S3 to an ECL instrument, using a PBS solution with a pH of 8 as an electrolyte and 50 μM triethylamine as a co-reactant, collecting the ECL signal intensity, with a PMT of 700 V and a potential range of 0.2 to 1.3 V, calculating the recovery value of the electrochemiluminescence signal, and calculating the corresponding alkaline phosphatase concentration according to the standard curve.
[0128] Example 12
[0129] The detection process of the electrochemiluminescence sensor system for determining alkaline phosphatase is as follows: S1, 300 μL of a mixed solution containing 25 mM AAP solution and alkaline phosphatase of different concentrations is prepared with a Tris-HCl buffer solution of pH=10; S2, the above solutions are mixed and reacted at 37°C for 40 minutes to obtain a solution containing AA; S3, the electrochemiluminescence sensor is placed in the solution obtained in the step S2 to react at room temperature for 5 minutes, taken out, washed with water, and blown dry with nitrogen for standby use; S4, the electrochemiluminescence sensor after the reaction in step S3 is connected to an ECL instrument, a PBS solution of pH=7.4 is used as an electrolyte and 100 μM triethylamine is used as a co-reactant, and the ECL signal intensity is collected, the PMT is 700 V, the potential range is 0.2-1.3 V, the recovery value of the electrochemiluminescence signal is calculated, and the corresponding alkaline phosphatase concentration is calculated according to the standard curve.
[0130] Embodiment 13
[0131] The linear relationship between the ΔECL intensity of the electrochemiluminescence sensor system for measuring adenosine triphosphate and the concentration of alkaline phosphatase. The detection process of the electrochemiluminescence sensor system is the same as that of Example 10.
[0132] Prepare different concentrations of alkaline phosphatase standard solutions, 10 -4 U / L, 10 -3 U / L, 10 -2 U / L, 10 -1 U / L, 1U / L, 10U / L, 10 2 U / L and 10 3 U / L, 3 parallel experimental groups were set for each concentration, and the detection method of Example 10 was used. The linear relationship analysis between the obtained △ECL signal intensity and the logarithmic value of alkaline phosphatase was performed, and the results are shown in Fig.15 As the concentration of alkaline phosphatase increases, the △ECL signal intensity gradually increases and shows a linear relationship. The linear range of the sensor is 10 -4 -10 2 U / L, the minimum detection limit is 8.1×10 -6 U / L, compared with the existing commercial alkaline phosphatase detection kit (spectrophotometric method, the minimum detection limit is 3U / L), the present invention has higher sensitivity.
[0133] Embodiment 14
[0134] Analysis of the specificity of target detection by an electrochemiluminescent sensor system for the determination of alkaline phosphatase.
[0135] The electrochemiluminescent sensor system of the present invention was investigated for non-specific response to the structural analogs of the target analyte. The detection process of the electrochemiluminescent sensor system was the same as that of Example 10, except that in step S1, 400 U / L of β-galactosidase, tyrosinase, glucose oxidase, horseradish peroxidase, catalase, and proteinase K were used instead of ALP. The results are shown in FIG. Fig.16 The ECL signal change of ALP is very obvious (40U / L), while the influence of other potential enzymes is negligible even when the concentration is 10 times higher than ALP (400U / L), indicating that the sensor designed in the present invention has good specificity.
[0136] Embodiment 15
[0137] The electrochemiluminescence sensor system of the present invention is used for quantitative detection of ALP in human serum.
[0138] In order to investigate the feasibility of the electrochemiluminescence sensor system of the present invention for quantitative detection of ATP in human serum, the detection process of the electrochemiluminescence sensor system is the same as that of Example 10. The preparation method of the ALP solution to be detected used in step S1 is as follows: dilute the ALP standard solution with 2 groups of 1% human serum solutions (solvent is 10mM Tris-HCl buffer, pH=8) to final concentrations of 0U / L, 0.005U / L, 0.5U / L and 5U / L, respectively, and set 3 parallel experimental groups for each concentration. The results are shown in FIG. Fig.17 As shown, the test results show that the recovery rate of the electrochemiluminescence sensor system of the present invention for detecting ALP in different human serum samples is distributed between 94.99% and 105.91%, and the relative standard deviation between different control groups is less than 5.5%, indicating that the test data of the sensor system is stable and reliable, and can be used for the determination of ALP in real biological samples.
[0139] In summary, the self-assembled copper nanoclusters prepared in the present invention significantly change the structure of the material and improve the performance of the material due to the existence of assembly behavior, so they have important application value in related fields such as catalysis, fluorescence (imaging) sensing, electrochemical sensing, light-emitting diodes, photoelectric conversion materials and biomedicine.
Claims
1. A method for preparing self-assembled copper nanoclusters, characterized in that: The following steps are involved: (1) dissolving a copper salt in an organic solvent to form a copper salt solution; (2) dissolving 4,6-dimethylthiopyrimidine in an organic solvent to form a 4,6-dimethylthiopyrimidine solution; (3) adding the 4,6-dimethylthiopyrimidine solution to the copper salt solution and stirring to obtain a mixed solution; (4) centrifuging the mixed solution, discarding the supernatant, and washing the precipitate; (5) adding water to the precipitate and stirring to obtain self-assembled copper nanoclusters.
2. The method for preparing the self-assembled copper nanoclusters according to claim 1, characterized in that: The copper salt in step (1) is copper nitrate, copper sulfate, copper chloride or copper carbonate.
3. The method for preparing the self-assembled copper nanoclusters according to claim 1, characterized in that: The copper salt in step (1) is copper nitrate trihydrate.
4. The method for preparing the self-assembled copper nanoclusters according to claim 1, characterized in that: In step (1), 10 to 60 mg of copper salt powder is mixed with 5 mL of organic solvent to form a copper salt solution; in step (2), 8 to 58 mg of 4,6-dimethylmercaptopyrimidine powder is mixed with 5 mL of organic solvent to form a 4,6-dimethylmercaptopyrimidine solution.
5. The method for preparing the self-assembled copper nanoclusters according to claim 1, characterized in that: The organic solvent in steps (1) and (2) is any one of methanol, ethanol, dimethyl sulfoxide and N,N-dimethylformamide.
6. The method for preparing the self-assembled copper nanoclusters according to claim 1, characterized in that: In step (3), the 4,6-dimethylthiopyrimidine solution is uniformly added to the copper salt solution under magnetic stirring, and the magnetic stirring is continued for 3 to 20 minutes to obtain a mixed solution.
7. The method for preparing the self-assembled copper nanoclusters according to claim 1, characterized in that: In step (4), the mixed solution is centrifuged at 1000-6000 rpm for 5 min, the supernatant is discarded, and the precipitate is washed to obtain the copper nanoclusters (DMPM-CuNCs) before self-assembly; in step (5), water is added to the precipitate and magnetic stirring is performed for 10-80 min to obtain the self-assembled copper nanocluster suspension (SA-DMPM-CuNCs).
8. A self-assembled copper nanocluster prepared by the method for preparing the self-assembled copper nanocluster according to claim 1.
9. Application of the self-assembled copper nanoclusters prepared by the method for preparing the self-assembled copper nanoclusters according to claim 1 in catalysis, fluorescence (imaging) sensing, light-emitting diodes, photoelectric conversion materials and biomedicine.
10. Use of the self-assembled copper nanoclusters prepared by the method for preparing the self-assembled copper nanoclusters according to claim 1 in preparing an electrochemiluminescent sensor for detecting alkaline phosphatase.
Citation Information
Cited By
Construction method and application of electrochemical luminescence biosensor based on cell membrane hydrogel antifouling interface
CN120446225A
Construction method and application of an electrochemiluminescence biosensor based on cell membrane hydrogel antifouling interface
CN120446225B
